Preparation and evaluation of injectable Rasagiline mesylate dual-controlled drug delivery system for the treatment of Parkinson's disease. (1st January 2018) - Jiang, Ying; Zhang, Xuemei; Mu, Hongjie; Hua, Hongchen; Duan, Dongyu; Yan, Xiuju; Wang, Yiyun; Meng, Qingqing; Lu, Xiaoyan; Wang, Aiping; Liu, Wanhui; Li, Youxin; et al.
Abstract: A microsphere–gel in situ forming implant (MS–Gel ISFI) dual-controlled drug delivery system was applied to a high water-soluble small-molecule compound Rasagiline mesylate (RM) for effective treatment of Parkinson's disease. This injectable complex depot system combined an in situ phase transition gel with high drug-loading and encapsulation efficiency RM–MS prepared by a modified emulsion-phase separation method and optimized by Box–Behnken design. It was evaluated for in vitro drug release, in vivo pharmacokinetics, and in vivo pharmacodynamics. We found that the RM-MS-Gel ISFI system showed no initial burst release and had a long period of in vitro drug release (60 days). An in vivo pharmacokinetic study indicated a significant reduction ( p < .01) in the initial high plasma drug concentration of the RM–MS–Gel ISFI system compared to that of the single RM–MS and RM– in situ gel systems after intramuscular injection to rats. A pharmacodynamic study demonstrated a significant reduction ( p < .05) in 6-hydroxydopamine-induced contralateral rotation behavior and an effective improvement ( p < .05) in dopamine levels in the striatum of the lesioned side after 28 days in animals treated with the RM–MS–Gel ISFI compared with that of animals treated with saline. MS-embedded in situ phase transition gel is superior for use as a biodegradable and injectable sustained drug delivery system with a low initial burst and long period of drug release for highly hydrophilic small molecule drugs.